Role of CYP3A4 in kinase inhibitor metabolism and assessment of CYP3A4 activity - Mikus, Gerd; Foerster, Kathrin (Translational cancer research, 2017)
Tyrosine kinase inhibitors (TKIs) are small pharmacologically active molecules, which are administered orally at fixed doses to combat tumor cells. Although oral administration is advantageous, the variability of exposure is important for drug efficacy. Hence, the impact of individual CYP3A activity as one of the most important enzymes regulating exposure is important to know. To assess the relevance of CYP3A’s contribution to the clearance of TKIs, 31 TKI European public assessment reports (EPAR) were evaluated. AUC ratios (AUCR) from drug-drug interactions studies with ketoconazole (strong CYP3A inhibitor) and rifampicin (strong CYP3A inducer) were calculated and a significant linear regression was found between both AUCRs (r 2 =0.6951) after nonlinear regression analysis of the log transformed data. In general, if CYP3A contributes to more than 50% to the overall clearance, dose adaptations should be applied. Phenotyping CYP3A by midazolam microdosing might be an applicable option in future to adjust the TKI dose to the individual CYP3A activity, which should then be validated by therapeutic drug monitoring (TDM) to achieve optimal—efficacious but non-toxic—drug concentrations.